THE FUNCTION OF ISLAMIC COUNSELING IN EDUCATION - Abdurrahman Abdurrahman (JURNAL HANDAYANI PGSD FIP UNIMED, 2020)
Abstract: Islamic counseling manifested in educational practices is directed at the accountability of educators and education personnel to foster students' personalities. The responsibility of coaching students not only carry out formal tasks, but rather the existence of accountability to Allah. This relationship is illustrated by the relationship between the teacher and students in reciprocity and the dedication to God which is used as an operational basis. It is this kind of relationship that is overlooked in the practice of education, especially Islamic education.Keywords: Islamic Counseling and EducationAbstrak: Konseling Islami yang termanifestasikan dalam praktik pendidikan diarahkan pada akuntabilitas tenaga pendidik dan kependidikan untuk membina kepribadian peserta didik. Tanggung jawab pembinaan peserta didik tidak hanya melaksnakan tugas formal, tetapi lebih kepada adanya akuntabilitas pada Allah Swt. Relasi ini tergambarkan pada hubungan antara guru denagn siswa secara timbal balik serta adanya pengabdian kepada Allah yang dijadikan sebagai landasan operasional. Relasi semacam inilah yang banyak terlewatkan dalam praktik pendidikan, khususnya pendidikan Islam. Kata Kunci : Konseling Islami dan Pendidikan